1997
DOI: 10.1016/s0969-2126(97)00267-0
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal arm exchange is observed in the 2.15 Å crystal structure of oxidized nitrite reductase from Pseudomonas aeruginosa

Abstract: Two ligands of hemes c and d1 differ between the two known NiR structures, which accounts for the fact that they have quite different spectroscopic and kinetic features. The unexpected domain-crossing by the N-terminal segment of NiR-Pa is comparable to that of 'domain swapping' or 'arm exchange' previously observed in other systems and may explain the observed cooperativity between monomers of dimeric NiR-Pa. In spite of having similar sequence and fold, the different kinetic behaviour and the spectral featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
187
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(192 citation statements)
references
References 64 publications
5
187
0
Order By: Relevance
“…The actual kinetic mechanism in AxNiR leading to the hyperbolic behavior may be much more complicated. The presented case of AxNiR is complicated by the fact that the observed inter-copper ET can also take place in the substrate- 5 For AfNiR (Alcaligenes faecalis S-6), a random-sequential mechanism has been postulated, in which the inter-copper ET precedes substrate binding at low nitrite concentrations but follows it at high nitrite concentrations (46). This suggestion, however, contradicts other findings indicating an inactivation of NiR with a prematurely reduced T2Cu center (14, 16, 19, 26, 27, 33).…”
Section: Steady-state Activity Of Axnir In H 2 O and D 2 O-mentioning
confidence: 99%
“…The actual kinetic mechanism in AxNiR leading to the hyperbolic behavior may be much more complicated. The presented case of AxNiR is complicated by the fact that the observed inter-copper ET can also take place in the substrate- 5 For AfNiR (Alcaligenes faecalis S-6), a random-sequential mechanism has been postulated, in which the inter-copper ET precedes substrate binding at low nitrite concentrations but follows it at high nitrite concentrations (46). This suggestion, however, contradicts other findings indicating an inactivation of NiR with a prematurely reduced T2Cu center (14, 16, 19, 26, 27, 33).…”
Section: Steady-state Activity Of Axnir In H 2 O and D 2 O-mentioning
confidence: 99%
“…It is, therefore, of great importance for the bacteria to regulate the concentration of NO. This regulation is achieved by the controlled expression of two enzymes, nitrite reductase (NiR) 4 and NO reductase. NiR reduces nitrite to produce NO (g) , and NO reductase reduces NO to N 2 O, where NO is the first gaseous compound in the pathway.…”
mentioning
confidence: 99%
“…NiR reduces nitrite to produce NO (g) , and NO reductase reduces NO to N 2 O, where NO is the first gaseous compound in the pathway. There are two main categories of NiRs; those that are heme-containing (cd1-NiRs) (3,4) and those that are copper-containing (Cu-NiRs) (5)(6)(7)(8). The overall enzymatic reaction performed by NiRs is NO 2 Ϫ ϩ 2H ϩ ϩ e Ϫ 3 NO (g) ϩ H 2 O. Cu-NiRs are blue or green in color, showing visible absorption at 460 and 600 nm (1).…”
mentioning
confidence: 99%
“…Earlier potentiometric and spectrophotometric titrations have suggested that cooperativity prevails in the interactions among heme sites in cd 1 NiRs isolated from Pseudomonas aeruginosa (Pa) (3) and Paracoccus pantotrophus (Pp) (4), yet the studies above failed to address their kinetic basis. Although all three enzymes show a marked homology in their amino acid sequences and, for the Pp and Pa proteins, also similarity in threedimensional structures, some noteworthy and intriguing structural differences have been observed that may imply significant differences in functional behavior (1,(5)(6)(7)(8): Heme-c Fe(III) in Pp-cd 1 NiR has His͞His axial ligands, whereas at the heme-d 1 Fe(III) the axial ligands are Tyr͞His (5). On reduction, the heme-c Fe(II) ligands switch to His͞Met concomitant with dissociation of the tyrosine ligand leaving the heme-d 1 Fe(II) penta-coordinated (7).…”
mentioning
confidence: 99%
“…A remarkable feature of Pa-cd 1 NiR enzyme is the ''arm exchange'' or ''domain swapping'' of its N-terminal tail that places Tyr-10 of one monomer close to the heme-d 1 site of the other one. Tyr-10 is hydrogen-bonded to the heme-d 1 hydroxide ligand, thereby preventing access of the substrate to the catalytic site (6). In contrast, no ''domain swapping'' occurs in Pp-cd 1 NiR, and Tyr-25 of the c-domain coordinates directly to the heme-d 1 iron of the same monomer (5).…”
mentioning
confidence: 99%